2013
DOI: 10.1177/2325957413510606
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Late Initiation of Highly Active Antiretroviral Therapy among Young HIV-Positive Men and Women Aged 18 to 29 Years in Canada

Abstract: Initiating highly active antiretroviral therapy (HAART) with low CD4 counts or AIDS-defining illnesses (ADIs) increases risk of treatment failure and death. We examined factors associated with late initiation among 18-to 29-year-olds within the Canadian Observational Cohort (CANOC) collaboration, a multi-site study of HIV-positive persons who initiated HAART after 2000. Late initiation was defined as beginning HAART with a CD4 count <200 cells/mm 3 and/or having a baseline ADI. Multivariable logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
3
13
1
Order By: Relevance
“…Consistent with prior results from BC, older age was associated with late and delayed ART initiation (Lourenco et al, 2015;Palmer et al, 2014). Notably, other research has found younger age to be associated with attrition in HIV care over time (Lourenco et al, 2014), suggesting a missed opportunity to retain younger people.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Consistent with prior results from BC, older age was associated with late and delayed ART initiation (Lourenco et al, 2015;Palmer et al, 2014). Notably, other research has found younger age to be associated with attrition in HIV care over time (Lourenco et al, 2014), suggesting a missed opportunity to retain younger people.…”
Section: Discussionsupporting
confidence: 82%
“…Key explanatory variables, established by previous research to impact timing of initiation (Cescon et al, 2015;Joseph et al, 2016;Lourenco et al, 2015;Palmer et al, 2014), included: sex at birth, age, ethnicity, HCV seropositivity, history of IDU, history of homelessness, and income. Additional variables included in this analysis were: physician advice regarding ART initiation, medical reasons for initiating ART, concerns about ART, and participant scores on the Antiretroviral Medication Attitude Scale (AMAS) (Viswanathan, Aanderson, & Thomas, 2005), the HIV Treatment Adherence Self-Efficacy Scale (HIV-ASES) (Johnson et al, 2007), and the Continuity of Care Scale (Uijen et al, 2012).…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…It bears mentioning that although the Patient Protection and Affordable Care Act offers great promise for the expansion of health coverage among young adults in particular (i.e., remaining on their parents’ insurance through age 26), there are data suggesting that even in universal access to no-cost care, late initiation of ART occurs among up to 40% of HIV+ men and women aged 18 to 29 years in Canada. 41 Thus, the delays in the initiation of ART or barriers to ART use may be beyond purely economic and also reflect a confluence of cultural, psychosocial, social, and structural etiologies that require further delineation.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported in Sub-Saharan Africa countries [34], these factors were incriminated to be responsible for the psychological impact causing a delay the HIV care [35][36][37]. In addition, the inducing role of fear of the knowledge of HIV positive status has been advocated [34] and was considered as a key barrier of utilisation of HIV testing services in Sub-Saharan Africa [38].…”
Section: Discussionmentioning
confidence: 93%